THE ROLE OF THE STORYTELLING APPROACH IN TEACHING ENGLISH AS A FOREIGN LANGUAGE (Scientific journal of the Fergana State University, 2023)
Language is a complex psychological process that cannot be evaluated and developed separately from thought or perception. Teachers and psychologists all over the world are very interested in the storytelling method, because the presentation of the material in the form of a story develops the attention and critical thinking of language learners, and at the same time increases the level of cultural education. Educational material presented as an interesting and exciting story helps to develop personal characteristics, shows the uniqueness of imagination in each student, allows to be active and show creativity. This article discusses the role of the storytelling approach in teaching English as a foreign language.